(untitled) (Bangladesh Journal of Medicine, 2024)
Hereditary spherocytosis (HS) is an autosomal dominant inherited hemolytic anemia that usually manifests in early adolescence. A very small proportion (5%) may undergo de novo mutations and present at an elderly age without any positive family history. The disease is characterized by anemia, jaundice, splenomegaly, and the presence of spherocytes in peripheral blood, which are osmotically fragile. A 55-year-old elderly male presented with generalized weakness and a history of repeated blood transfusions for 5 months. He had recurrent jaundice for 8 years. There was no relevant family or drug history. He was anemic, icteric, and had mild splenomegaly. Investigation revealed persistently low Hb with normal red cell indices. There were a lot of spherocytes with polychromasia on the peripheral blood film. There was also evidence of hemolysis with a high reticulocyte count and higher levels of total and indirect bilirubin. Autoimmune hemolysis was excluded by negative direct and indirect Coomb’s tests, and Hb defect was excluded by normal Hb electrophoresis. We also ruled out other infectious causes. The ultrasound confirmed splenomegaly. The osmotic fragility test showed increased osmotic fragility of the patient’s red cells. History, symptoms, and test results strongly point to autosomal dominant hereditary spherocytosis with new mutations. An eosin-5-Maleimide binding test was advised, along with family screening of the patient. Bangladesh J Medicine 2024; 35: 110-113